Periostin/Filamin-A: A Candidate Central Regulatory Axis for Valve Fibrogenesis and Matrix Compaction - Misra, Suniti; Ghatak, Shibnath; Moreno-Rodriguez, Ricardo A.; Norris, Russell A.; Hascall, Vincent C.; Markwald, Roger R. (Frontiers in Cell and Developmental Biology, 2021)
Background Discoveries in the identification of transcription factors, growth factors and extracellular signaling molecules have led to the detection of downstream targets that modulate valvular tissue organization that occurs during development, aging, or disease. Among these, matricellular protein, periostin, and cytoskeletal protein filamin A are highly expressed in developing heart valves. The phenotype of periostin null indicates that periostin promotes migration, survival, and differentiation of valve interstitial cushion cells into fibroblastic lineages necessary for postnatal valve remodeling/maturation. Genetically inhibiting filamin A expression in valve interstitial cushion cells mirrored the phenotype of periostin nulls, suggesting a molecular interaction between these two proteins resulted in poorly remodeled valve leaflets that might be prone to myxomatous over time. We examined whether filamin A has a cross-talk with periostin/signaling that promotes remodeling of postnatal heart valves into mature leaflets. Results We have previously shown that periostin/integrin-β1 regulates Pak1 activation; here, we revealed that the strong interaction between Pak1 and filamin A proteins was only observed after stimulation of VICs with periostin; suggesting that periostin/integrin-β-mediated interaction between FLNA and Pak1 may have a functional role in vivo. We found that FLNA phosphorylation (S2152) is activated by Pak1, and this interaction was observed after stimulation with periostin/integrin-β1/Cdc42/Rac1 signaling; consequently, FLNA binding to Pak1 stimulates its kinase activity. Patients with floppy and/or prolapsed mitral valves, when genetically screened, were found to have point mutations in the filamin A gene at P637Q and G288R. Expression of either of these filamin A mutants failed to increase the magnitude of filamin A (S2152) expression, Pak1-kinase activity, actin polymerization, and differentiation of VICs into mature mitral valve leaflets in response to periostin signaling. Conclusion PN-stimulated bidirectional interaction between activated FLNA and Pak1 is essential for actin cytoskeletal reorganization and the differentiation of immature VICs into mature valve leaflets.